1994
DOI: 10.1177/036354659402200303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lateral Ankle Ligamentous Reconstruction Procedures

Abstract: The static restraints of various surgical procedures for chronic lateral ankle instability were compared. Forty cadaveric ankles were divided equally into the following five groups: 1) ankles with intact anterior talofibular and calcaneofibular ligaments, 2) ankles with incised anterior talofibular and calcaneofibular ligaments, 3) ankles with Chrisman-Snook procedure, 4) ankles with Watson-Jones procedure, or 5) ankles with modified Broström procedure. All ankles were placed in a mechanical apparatus for ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 23 publications
3
75
0
5
Order By: Relevance
“…The functional results in both groups were good between 2 and 4 years after surgery. These results are comparable with many previous reports [4,8,12,14,16,17].…”
Section: Discussionsupporting
confidence: 93%
“…The functional results in both groups were good between 2 and 4 years after surgery. These results are comparable with many previous reports [4,8,12,14,16,17].…”
Section: Discussionsupporting
confidence: 93%
“…The most common techniques are the non-anatomical Evans, the Watson-Jones, and the Chrisman-Snook, which make use of the tendon of peroneus brevis for reconstruction. The success rate is about 90% with these methods [13,21,24], but these techniques can be criticised as they use non-anatomical graft passage sites and are followed by residual limitation of subtalar joint movements and chronic pain. Sural nerve injury is also reported in 14 patients treated by the ChrismanSnook technique [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the long-term, it seems that the results of anatomical reconstruction methods of the lateral ankle ligaments are superior to non-anatomical methods, as they achieve better stability and cause less degenerative arthritis [11,12,19,21]. Krips has reported that after 30 years the Evans tenodesis did not adequately prevent laxity, thus allowing development and progression of osteoarthritis of the ankle and subtalar joints [20].…”
Section: Discussionmentioning
confidence: 99%
“…[9,[13][14][15] In a cadaveric study comparing the modified Broström-Gould procedure to tendon reconstruction procedures, Liu et al found that the anatomic repair technique resulted in less loss of motion in addition to greater mechanical restraint. [17] In a retrospective review of 54 patients, Krips et al found that the modified Broström-Gould procedure was superior to tendon reconstructive procedures in terms of final stability as determined through stress radiographs and clinical outcomes. [25] While all surgical treatments should be tailored to the individual patient, the modified Broström-Gould procedure restores the native anatomy, has demonstrated efficacy both in the lab and in the clinic, and should be one of the procedures in the armamentarium of orthopaedic surgeons who treat lateral ankle instability.…”
Section: Discussionmentioning
confidence: 99%